Expression of Concern Notice: Research on Intelligent Analysis Method for the Impact of Running APP Software on Physical Fitness Indicators of College Students - Wang, Jing (EAI Endorsed Transactions on Pervasive Health and Technology, 2026)
We, the publisher, are issuing an expression of concern about Jing Wang (2024) Research on Intelligent Analysis Method for the Impact of Running APP Software on Physical Fitness Indicators of College Students. https://doi.org/10.4108/eetpht.10.5506 There is a concern over the integrity of the peer review review process and suspected manipulation of the editorial process. The investigation is ongoing and we advise scholars to exercise caution when referencing this manuscript.